A review of the prospects for vaccination in African trypanosomiasis. Parts I, II - Murray, M.; Barry, J.D.; Morrison, W. Ivan; Williams, R.O.; Hirumi, H.; Rovis, L. (Food and Agriculture Organization of the United Nations, 1983)
Reviews prospects of vaccination against African trypanosomiasis, mentioning constraints in developing a vaccine, and current knowledge on the molecular biology of the trypanosome and on antigenic variation with respect to possible future vaccines. Describes possible regimes for immunological intervention, including the immunogenicity and cross reactivity of trypanosome subcellular fractions, reduction of host susceptibility to African trypanosomes by the non-specific use of immunostimulants or chemotherapy.